Abnormalties in platelet reactivity in pre-eclampsia. (18th April 2012) - Murray, A; Burke, N; Flood, K; Dempsey, M; Fay, L; Fonseca-Kelly, Z; Cotter, B; Donnelly, J; Geary, M; Kenny, D; Malone, F
Abstract : Forty patients diagnosed with either pre-eclamspia or gestational hypertension were recruited. Inclusion criteria were singleton pregnancies between 24+0 and 39+6 with either pre-eclampsia or gestational hypertension as defined by ACOG criteria. Exclusion criteria included diabetes, clotting disorders, aspirin usage or BMI >30. Patients were in the third trimester of pregnancy and the values obtained were compared to patients (N=30) who were in the third trimester of uncomplicated 'normal' pregnancy. A 30ml whole blood sample was drawn according to a strict protocol to maintain platelet integrity. A platelet function assay was performed on each sample within 30 minutes of blood draw. A modification of standard light transmission aggregometry was used to assess platelet function, with light absorbance measured following addition of 5 different agonists at maximal and sub-maximal concentrations. Since platelets have multiple receptors it is necessary to study more than one receptor with the various agonists. The percentage aggregation response for each concentration of each agonist was calculated. Platelet reactivity differed significantly between the two groups of patients for each agonist. Platelet aggregation to arachidonic acid (p<0.0042), epinephrine (p<0.00001) and collagen (p<0.00001) was less reactive in pre-eclamptic and gestational hypertension than in uncomplicated third trimester patients. This pattern of platelet aggregation was not repeated for the agonists TRAP and ADP. We have demonstrated a significant reduction in platelet reactivity in patients with both pre-eclampsia and gestational hypertension compared to patients with uncomplicated pregnancies in the third trimester. These data may be of value when designing interventions for prevention or treatment of pre-eclampsia.